Phase II study of preoperative chemoradiation with S‐1 plus oxaliplatin in patients with locally advanced rectal cancer - Lee, Eun Mi (Cancer Sci, 2012)
A phase II study of preoperative chemoradiation (CRT) with S‐1 plus oxaliplatin in patients with locally advanced rectal cancer was conducted. The total radiotherapy dose was 50.4 Gy. Chemotherapy consisted of oxaliplatin 50 mg/m(2) on days 1, 8, 22 and 29 and S‐1 80 mg/m(2) per day on days 1–14 and 22–35. The tumor apparent diffusion coefficient (ADC) was measured using diffusion‐weighted magnetic resonance imaging (DW‐MRI) before and after CRT. Total mesorectal excision was performed within 6 ± 2 weeks. The primary end‐point was the pathological complete response (pCR) rate. A total of 38 patients were enrolled. The pCR rate was 22.9% (8/35; 95% CI, 10.9–42.1), and 10 (28.6%) patients showed near‐total tumor regression. There was no grade 4 adverse event, and grade 3 adverse events included leukopenia (5.4%), diarrhea (5.4%), anorexia (2.7%) and nausea (2.7%). The tumor ADC was calculated in 38 patients (including those who participated in the phase I study). The post‐CRT ADC (P = 0.037) and the percentage change in ADC (P = 0.026) were significantly correlated with pathological response. In conclusion, preoperative CRT with S‐1 plus oxaliplatin showed promising results in pathological responses and favorable toxicity profiles. (Cancer Sci 2013; 104: 111–115)